TESTING THE HOMOGENEOUS INTEREST RATES ASSUMPTION BY PRINCIPAL COMPONENT ANALYSIS: THE EURO AREA CASE - Stelmach, Jerzy (Ekonomika, 2010)
Although there are many different interest rates in the economy, in theoretical and applied model building these distinctions are usually ignored by assuming that there is only one, “true” interest rate. Hence, the aim of this article is twofold. First, we empirically examine whether such assumption is plausible for the Euro area yield curve data. Second, using different time spans we try to assess the impact of the financial crisis on the validity of this assumption. For both purposes, the principal component analysis technique will be employed.